Pornography in The Perspective of Islamic and National Law - Hayati, Ilda; Edyar, Busman (AJIS: Academic Journal of Islamic Studies, 2024)
This research aims to explain the perspective of Islamic and national law on pornography. This is a normative juridical research with a comparative approach which is analyzed by prescriptive analysis. The results of the research show that Islamic and national law have the same paradigm towards pornography as a despicable act which is prohibited by sharia and the constitution. There are at least two terms in Islamic law that have intersections with pornography; first, the term aurat, which is a part of the human body that should not be shown or must be covered because it can cause shame (QS.24: 58) and arouse the sexual desires of others who see it (QS.33: 59). Secondly, tabarruj, which describes a person in a dress that tends to be indecent or characterizes the appearance of a dishonorable person. Meanwhile, national law regulates this pornography in several regulations such as Law No. 44/2008 on Pornography; several articles in the Criminal Code; Law No. 32/2002 on Broadcasting; Law No. 8/1992 on Film; Law No. 40/1999 on Press; Law No. 36/1999 on Telecommunications; and Law No.11/2008 on Information and Electronic Transactions.